Investigation Of Roadside Wind Energy The Harvesting Mechanism - Sathiaseelan, Nagentheran (Universiti Sains Malaysia, 2021)
Wind is another alternative form of renewable energy that has been harvested since 1800s. Common conventional modes of wind energy harvesting technologies are the horizontal-axis wind turbine (HAWT) and vertical-axis wind turbine (VAWT). For roadside wind energy harvesting, VAWT can be considered to harness the unused energy produced from car wakes and vortex. However, height and optimal blade design of VAWT limits the operational performance to deliver power at higher efficiencies. Therefore, this project aimed to study a new unconventional roadside wind energy harvesting mechanism. A rectangular polyester sail fabric was considered as wind energy harvester material. The optimal wind energy harvesting mechanism, two-way to one-way conversion mechanism and gearbox mechanism were designed in SOLIDWORKS to generate useful output power. The sail fabric was simulated in ANSYS AIM 19.2 Workbench to obtain lift forces acting on it when a vehicle passes by. Effect of number of vehicles and distance between each vehicle were studies in this project. The ANSYS simulation results of the sail fabric were validated with theoretical approach of a thin flat plat with airflow flowing parallel to it. The simulated results were used in SOLIDWORKS motion analysis to analyze amount of power generated. The harvesting mechanism produced maximum output power of 37.3278W without any generator coupling. The optimum point of the harvesting mechanism was observed at lift force of 45N to produce peak power and torque. The power and torque were observed to reduce after lift force of 45N complying the rotational speed-torque relationship. A direct-drive generator performance chart was used to estimate the output power to boost it. Overall, the harvesting mechanism energy density of 24.9 W/m2 for a sail fabric area approximately 1.5m2.